Antebellum at Sea : Maritime Fantasies in Nineteenth-Century America - Berger, Jason, 1976- (Book collections on Project MUSE., 2012)
In the antebellum years, the Western world's symbolic realities were expanded and challenged as merchant, military, and scientific activity moved into Pacific and Arctic waters. In Antebellum at Sea, Jason Berger explores the roles that early nineteenth-century maritime narratives played in conceptualizing economic and social transitions in the developing global market system and what these chronicles disclose about an era marked by immense change. Focusing on the work of James Fenimore Cooper and Herman Melville, Berger enhances our understanding of how the nineteenth cen.